Grade 12 Students’ Perceptions of Distance Learning in General Chemistry Subject: An Evidence from the Philippines (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
The onslaught of the COVID-19 pandemic forces institution to close face-to-face classes, thereby resulting to a paradigm shift towards remote learning. Unconventional learning strategies were reinforced to continuously provide education amidst the crisis. This led to the conversion of classroom-oriented learning resources into learning resources adapted to distance learning. At present, the placement of alternative learning modalities in a new normal classroom setting has become a mainstream point of discussion in the education sector. In light of the new trend in education brought by the pandemic or other similar circumstances, this study aims to identify students’ perceptions regarding the utilization of synchronous and asynchronous distance learning resources in Grade 12 level. It also highlighted students’ preferences regarding the synchronous and asynchronous mode of delivering instructions. The participants were randomly selected 317 Grade 12 students enrolled in Special Health Sciences STEM track from a private medical institution situated in an urban area of Cavite in the Philippines. These Grade 12 students had immersed experience in synchronous online classes along with asynchronous learning activities. A dependent sample t-test was used to find out difference between the use of synchronous and asynchronous learning modalities. Conceptual understanding of students was measured based on their performance on summative assessments both in synchronous and asynchronous modalities. Descriptive statistics and thematic analysis were also used to present students’ evaluation on the different distance learning aspects particularly on the teaching approach, learning materials and instructions, activities, and assessments. Results revealed that students have high interest on the teaching approach in asynchronous modality consistent with obtaining better performance in the asynchronous assessment. Students valued the asynchronous threaded discussions, the availability of relevant learning materials, and teacher’s guidance and scaffolding on the learning process as essential components of distance learning (synchronous or asynchronous).